Memahami Risiko Investasi dan Cara Mengelolanya Dengan Bijak - Putri, Arni Eza; Mulyana, Asep; Sabrina, Eka Putri Hana; M, Mariam; Suherman, Ujang (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Investment is part of improving welfare in the future to anticipate the inflation that occurs every year. Besides being profitable, investment is also very risky which can occur simultaneously or alone so we must be able to manage it properly. This article aims to find out how to understand the risks and how to manage them wisely. The research method used is descriptive, by collecting secondary data whose data comes from various sources such as scientific literature, articles and so on. Investment risk can come from many factors and that risk cannot be eliminated, so before investing we must understand these risks and have several considerations and strategies. So that the investment that we manage can get a good profit by reducing these risks. Because each risk has a different increase, so that by reducing the risk, the investment we do will be managed wisely and will get maximum profit.